Is knowledge of HIV status associated with sexual behaviours?: a fixed effects analysis of a female sex worker cohort in urban Uganda - Ortblad, Katrina; Musoke, Daniel K.; Ngabirano, Thomson; Salomon, Joshua A.; Haberer, Jessica E.; McConnell, Margaret; Oldenburg, Catherine E.; Bärnighausen, Till (Journal of the International AIDS Society, 2019)
Introduction Female sex workers (FSWs) have strong economic incentives for sexual risk-taking behaviour. We test whether knowledge of HIV status affects such behaviours among FSWs. Methods We used longitudinal data from a FSW cohort in urban Uganda, which was formed as part of an HIV self-testing trial with four months of follow-up. Participants reported perceived knowledge of HIV status, number of clients per average working night, and consistent condom use with clients at baseline, one month, and four months. We measured the association between knowledge of HIV status and FSWs’ sexual behaviours using linear panel regressions with individual fixed effects, controlling for study round and calendar time. Results Most of the 960 participants tested for HIV during the observation period (95%) and experienced a change in knowledge of HIV status (71%). Knowledge of HIV status did not affect participants’ number of clients but did affect their consistent condom use. After controlling for individual fixed effects, study round and calendar month, knowledge of HIV-negative status was associated with a significant increase in consistent condom use by 9.5 percentage points (95% CI 5.2 to 13.5, p < 0.001), while knowledge of HIV-positive status was not associated with a significant change in consistent condom use (2.5 percentage points, 95% CI −8.0 to 3.1, p = 0.38). Conclusions In urban Uganda, FSWs engaged in safer sex with clients when they perceived that they themselves were not living with HIV. Even in communities with very high HIV prevalence, the majority of the population will test HIV-negative. Our results thus imply that expansion of HIV testing programmes may serve as a behavioural HIV prevention measure among FSWs.
Gesehen am 23.07.2020